2019
DOI: 10.1021/jacs.9b03726
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Redox Non-innocence Inducing Stepwise Oxidative Addition Reaction: Nitrosoarene C–N Bond Cleavage on Low-Coordinate Cobalt(0) Species

Abstract: The reactions of nitrosoarenes with transition-metal species are fundamentally important for their relevance to metal-catalyzed transformations of organonitrogen compounds in organic synthesis and also the metabolization of nitroarenes and anilines in biology. In addition to the well-known reactivity of metal-mediated N−O bond activation and cleavage of nitrosoarenes, we present herein the first observation of a nitrosoarene C−N bond oxidative addition reaction upon the interaction of a three-coordinate cobalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 63 publications
0
14
1
Order By: Relevance
“…Noting that steric congestion within [(IMes)­Co­(η 2 :η 2 -dvtms)] might prevent the approach of the C­(sp 3 )–H bonds of IMes to the cobalt center, which will render the formation of cyclometalated intermediates en route to 1 difficult, and that the N-aryl substituents of NHCs can incur arene···metal interactions with electron-rich metal centers, ,, the dearylation reaction observed in the current study might result from an intramolecular C–N bond oxidative addition reaction of the cobalt­(−I) intermediate [K­(18-crown-6)]­[(IMes)­Co­(η 2 :η 2 -dvtms)] ( A ) that can be formed from one-electron reduction of [(IMes)­Co­(η 2 :η 2 -dvtms)] (Scheme ). Examples of C–N bond oxidative addition reactions , of cobalt species were found in the interaction of CpCo I species with isocyanides and (IPr)­Co 0 species with a nitrosoarene . Then the homolytic cleavage of the Co–C­(mesityl) bond in B could give 1 and a mesityl radical.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noting that steric congestion within [(IMes)­Co­(η 2 :η 2 -dvtms)] might prevent the approach of the C­(sp 3 )–H bonds of IMes to the cobalt center, which will render the formation of cyclometalated intermediates en route to 1 difficult, and that the N-aryl substituents of NHCs can incur arene···metal interactions with electron-rich metal centers, ,, the dearylation reaction observed in the current study might result from an intramolecular C–N bond oxidative addition reaction of the cobalt­(−I) intermediate [K­(18-crown-6)]­[(IMes)­Co­(η 2 :η 2 -dvtms)] ( A ) that can be formed from one-electron reduction of [(IMes)­Co­(η 2 :η 2 -dvtms)] (Scheme ). Examples of C–N bond oxidative addition reactions , of cobalt species were found in the interaction of CpCo I species with isocyanides and (IPr)­Co 0 species with a nitrosoarene . Then the homolytic cleavage of the Co–C­(mesityl) bond in B could give 1 and a mesityl radical.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Examples of C−N bond oxidative addition reactions 44,45 of cobalt species were found in the interaction of CpCo I species with isocyanides 46 and (IPr)Co 0 species with a nitrosoarene. 47 Then the homolytic cleavage of the Co−C(mesityl) bond in B could give 1 and a mesityl radical. This step might be reminiscent of the decomposition reactions of the cyclic (alkyl)(amino)carbene cobalt(I) species (cAAC) 2 CoR (R = Me, Ph) that gave (cAAC) 2 Co and radicals R. 48 The mesityl radical can readily perform a hydrogen atom abstraction reaction with the solvent to produce mesitylene, which was detected by GC analysis in 48% GC yield (see Figure S4 in the Supporting Information).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The solid sample of 9 has a magnetic momentum of 2.90 μB at room temperature (Figure S3), which is comparable to those of the NHCCo(0)alkene complexes (2.8–3.3(1) μB). The structure of 9 established by X-ray diffraction study shows a C 2 molecular symmetry (Figure ). The two C alkyne atoms of the alkyne ligand are coplanar with the cobalt center and the two C carbene atoms.…”
Section: Resultsmentioning
confidence: 76%
“…Structurally authenticated cobalt(0) complexes with coordination numbers of less than 4 are relatively scarce and were only known very recently (Chart ). We reported that the combined ligand set of N -heterocyclic carbene with vinylsilanes is effective in stabilizing three-coordinate cobalt(0) complexes in the forms of (NHC) n Co­(CH 2 CHSiR 3 ) x ( n = 1, x = 2; n = 2, x = 1, Chart ). These NHC–cobalt(0)–vinylsilane complexes show rich reactivity toward organic azides, hydrosilanes, hydrophosphines, and nitrosoarenes, giving cobalt imido, silyl, phosphido, and nitrosyl complexes, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation